Cinética da reação de conversão de etanol em 1,3-butadieno empregando catalisadores multifuncionais - Da Ros, Simoní (2017)
The catalytic conversion in gas phase of ethanol into 1,3-butadiene (1,3-BD) was investigated over the heterogeneous catalysts MgO-SiO2, ZrO2 and ZnO containing MgO-SiO2, and alkali metal doped ZrO2-ZnO/MgO-SiO2 prepared by co-precipitation. For the first time, the kinetics of this reactional system was evaluated employing the information contained in the covariance matrix of experimental measurements, which allowed indentifying a modification of the mechanism as reaction temperature increased: from 300 to 400 ºC, the rate-limiting step was suggested as the acetaldehyde condensation, while at 450 ºC, ethanol dehydrogenation step limited the process. Besides, the characterization of the covariance matrix of experimental fluctuations, using different reaction conditions and catalysts, demonstrated that both reaction temperature and catalyst properties affected experimental fluctuations. It was also shown that the co-precipitation method was appropriate for preparation of catalysts able to achieve high 1,3-BD productivities. Moreover, catalyst acidity was modified through the addition of alkali metals (Na, K and Li), allowing for the minimization of parallel reactions of ethanol dehydration to ethene and diethyl ether. Thus, a new catalyst was developed, which allowed for the increasing of the combined 1,3-BD and acetaldehyde selectivity up to 72 mol %. Finally, the effects of reaction variables, temperature and spatial velocity, were investigated with help of a statistical design, employing the developed catalysts. Results indicated that high 1,3-BD yields may be achieved at high spatial velocities conditions, as long as ethanol partial pressure be kept high, improving the potential of industrial application of this process.